2024
DOI: 10.1101/2024.02.22.581596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling Movement Intention after Stroke: Integrating EEG and EMG for Motor Rehabilitation

Eduardo López-Larraz,
Andrea Sarasola-Sanz,
Niels Birbaumer
et al.

Abstract: Detecting attempted movements of a paralyzed limb is a key step for neural interfaces for motor rehabilitation and restoration after a stroke. In this paper, we present a systematic evaluation of electroencephalographic (EEG) and electromyographic (EMG) activity to decode when stroke patients with severe upper-limb paralysis attempt to move their affected arm. EEG and EMG recordings of 35 chronic stroke patients were analyzed. We trained classifiers to discriminate between rest and movement attempt states rely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that EEG and EMG signals provide complementary information (Balasubramanian et al, 2018;López-Larraz et al, 2024). However, the relationship between brain and muscle activations remains challenging to understand and characterize.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that EEG and EMG signals provide complementary information (Balasubramanian et al, 2018;López-Larraz et al, 2024). However, the relationship between brain and muscle activations remains challenging to understand and characterize.…”
Section: Discussionmentioning
confidence: 99%